2017
DOI: 10.1016/j.jcjo.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of novel PAX6 gene abnormalities in aniridia and clinical presentation

Abstract: The number of PAX6 mutations associated with aniridia continues to increase. Variable foveal architecture despite nearly identical anterior segment disease in 4 participants with an Ex9 ELP4-Ex4 DCDC1 deletion suggested that molecular cues causing variation in disease in the posterior segment differ from those at play in the anterior segment. Results in 3 patients without identifiable PAX6 mutations and a review of the literature suggest that such cases be described as phenocopies rather than actual cases of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
3
18
0
1
Order By: Relevance
“…4 The subsets of grade 1 do not apply to the cohort reported by Casas-Llera et al, as they only detected grade 2-4 foveal hypoplasia, furthermore we note that their paper was submitted before our latest paper was published. Interestingly, a previous paper by Sannan et al 5 reported a full spectrum of grade 0-4 foveal hypoplasia in a large cohort of PAX6 mutations.…”
Section: Dear Editormentioning
confidence: 97%
“…4 The subsets of grade 1 do not apply to the cohort reported by Casas-Llera et al, as they only detected grade 2-4 foveal hypoplasia, furthermore we note that their paper was submitted before our latest paper was published. Interestingly, a previous paper by Sannan et al 5 reported a full spectrum of grade 0-4 foveal hypoplasia in a large cohort of PAX6 mutations.…”
Section: Dear Editormentioning
confidence: 97%
“…By contrast, missense mutations usually exhibit a moderate impact on PAX6 functionality and are often associated with some atypical PAX6 -associated phenotypes, such as mild forms of iris coloboma or isolated foveal hypoplasia, or more severe phenotypes of Peter’s anomaly and microphthalmia ( Hanson et al, 1999 ; Azuma et al, 2003 ; Nallathambi et al, 2006 ; Jia et al, 2010 ; Thomas et al, 2014 ). However, no obvious genotype-phenotype correlations have been established to date ( Gupta et al, 1998 ; Gronskov et al, 1999 ; Dubey et al, 2015 ; Sannan et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… 15 Recently, a phase 2 clinical trial has begun for the treatment of aniridia patients using a topical formulation of the drug, Ataluren (ClinicalTrials.gov: NCT02647359 ). 16 Ataluren targets the mutant allele by suppressing premature stop codons created by nonsense mutations. 17 Therefore, its potential efficacy is limited to those patients with premature stop mutations where substitution with another amino acid does not disrupt the function of the protein.…”
Section: Introductionmentioning
confidence: 99%